A Theranostic Nanoprobe for Hypoxia Imaging and Photodynamic Tumor Therapy - Fan, Jing Hao; Fan, Gui Ling; Yuan, Ping; Deng, Fu An; Liu, Ling Shan; Zhou, Xiang; Yu, Xi Yong; Cheng, Hong; Li, Shi Ying (Frontiers in Chemistry, 2019)
Hypoxia is a common feature for most malignant tumors, which was also closely related to the oxygen-dependent photodynamic therapy. Based on Fӧrster resonance energy transfer (FRET), a smart nanoprobe (designated as H-Probe) was designed in this paper for hypoxia imaging and photodynamic tumor therapy. Due to the FRET process, H-Probe could respond to hypoxia with a significant fluorescence recovery. Moreover, abundant in vitro investigations demonstrated that the photosensitizer of PpIX in H-Probe could generate large amounts of singlet oxygen to kill cancer cells in the presence of oxygen and light with appropriate wavelength. Also, intravenously injected H-Probe with light irradiation achieved an effective tumor inhibition in vivo with a reduced side effect. This original strategy of integrating hypoxia imaging and tumor therapy in one nanoplatform would promote the development of theranostic nanoplatform for tumor precision therapy.